Peran Gembala Menghadapi Deviasi Alkitab terkait Kultur di Era Abad ke-21: Analisis teks 1 Timotius 1:3-5 - Tanani, Stefany Sabrina; Gultom, Mawar Juwita; Sugiono, Sugiono (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Abstract: Heresies are teachings that deviate from the Bible. This teaching has appeared since the first century until now. As time goes by and the church develops, the problem of Bible deviations related to culture in the 21st century era becomes increasingly complex. In fact, some of these deviations are already integrated into the cultural traditions of the congregation's neighborhood. The aim of this scientific work is to discover the role of the pastor in dealing with Biblical deviations related to culture according to Paul's teachings and apply it to shepherd in the 21st century era. This scientific work will be prepared by applying qualitative research methods with a hermeneutic and literary study approach. The results obtained in the research were the discovery of the right attitude in facing heretical teachings according to 1 Timothy 1:3-5, namely that a community must have one leader (verse 3), must have the courage to make apologetics with heretical teachers (verse 4), face it with love that arises. from a pure conscience and sincere faith (verse 5). Meanwhile, the recommended implication is that the pastor is able to guide the congregation so that it does not fall deeper into a deviant culture, is able to direct the congregation to a life style of salvation given by God in faith, and is able to collaborate with the congregation to develop a good culture. Abstrak: Ajaran sesat merupakan ajaran yang menyimpang dari Alkitab. Ajaran ini sudah muncul sejak abad pertama sampai sekarang ini. Seiring berjalannya masa dan berkembangnya gereja, masalah deviasi Alkitab terkait kultur di era abad ke-21menjadi semakin kompleks. Bahkan beberapa dari penyimpangan tersebut sudah ada yang menyatu dengan tradisi budaya di lingkungan tinggal jemaat. Tujuan dari  Penelitian ini ialah menemukan peran gembala dalam menghadapi deviasi Alkitab terkait dengan kultur menurut ajaran Paulus dan menerapkannya kepada gembala di era abad ke-21.  Penelitian ini akan disusun dengan menerapkan metode penelitian kualitatif dengan suatu pendekatan studi hermeneutik dan leteratur. Hasil yang diperoleh dalam penelitian ialah ditemukanya sikap yang tepat dalam menghadapi ajaran sesat menurut 1 timotius 1:3-5 yakni satu komunitas harus memiliki satu pemimpin (ayat 3), harus berani berapologetika dengan pengajar sesat (ayat 4), menghadapi dengan kasih yang timbul dari hati nurani yang murnidan iman yang ikhlas (ayat 5). Sedangkan implikasi yang direkomendasikan ialah gembala mampu memandu jemaat agar tidak jatuh lebih dalam ke kultur yang menyimpang, mampu mengarahkan jemaat kepada tata hidup keselamatan yang diberikan Allah dalam iman, dan mampu berkolaborasi dengan jemaat untuk mengembangkan kultur yang baik.